Intraocular Pressure and Anterior Segment Morphometry Changes after Uneventful Phacoemulsification in Type 2 Diabetic and Nondiabetic Patients - João N. Beato; David Reis; João Esteves-Leandro; Manuel Falcão; Vítor Rosas; Ângela Carneiro; Fernando Falcão Reis (Journal of Ophthalmology)
Purpose. To compare intraocular pressure (IOP) and anterior segment (AS) morphometry changes after uneventful phacoemulsification between nonglaucomatous eyes with open-angles from patients with and without type 2 diabetes mellitus (DM) and determine which factors may predict greater IOP-lowering effect. Methods. Forty-five diabetic (45 eyes) and 44 (44 eyes) age- and sex-matched non-DM patients with age-related cataract were enrolled in this prospective observational study. Goldmann applanation tonometry and AS Scheimpflug tomography (Pentacam® HR) were performed preoperatively and at 1- and 6-month follow-up. Linear regression analysis was performed to evaluate the clinical variables related to postoperative IOP changes at 6 months. Results. There was a significant postoperative IOP reduction 6 months after surgery (p<0.001) by an average of 2.9 ± 2.9 mmHg (15.5%) and 2.4 ± 2.8 mmHg (13.0%) in the DM group and non-DM groups (p=0.410), respectively. All AS parameters (anterior chamber depth, volume, and angle) increased significantly postoperatively (p<0.001). Multivariate linear regression analysis showed that higher preoperative IOP was significantly associated with IOP reduction at 6-month follow-up (p<0.05). Conclusion. Nonglaucomatous eyes with open-angles from both type 2 diabetic and nondiabetic patients experienced similar AS changes and IOP reductions following uneventful phacoemulsification, and this IOP-lowering effect was strongly correlated with preoperative IOP.